2008
DOI: 10.4049/jimmunol.180.9.6054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IL-10-Secreting T Cells Derived from Regulatory CD4+CD25+ Cells by the TIRC7 Surface Marker

Abstract: Natural CD25+CD4+ regulatory T cells (Treg) are essential for self-tolerance and for the control of T cell-mediated immune pathologies. However, the identification of Tregs in an ongoing immune response or in inflamed tissues remains elusive. Our experiments indicate that TIRC7, T cell immune response cDNA 7, a novel membrane molecule involved in the regulation of T lymphocyte activation, identifies two Treg subsets (CD25lowTIRC7+ and CD25highTIRC7−) that are characterized by the expression of Foxp3 and a supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…During tumor progression, Tregs accumulate in tumors and secondary lymphoid organs (18,28). It has been suggested that the CCL22 produced by tumor cells or associated macrophages recruits Tregs into the tumor bed (39).…”
Section: Discussionmentioning
confidence: 99%
“…During tumor progression, Tregs accumulate in tumors and secondary lymphoid organs (18,28). It has been suggested that the CCL22 produced by tumor cells or associated macrophages recruits Tregs into the tumor bed (39).…”
Section: Discussionmentioning
confidence: 99%
“…ϩ monocytes/macrophages and CD4 ϩ CD25 ϩ T cells Monocyte/macrophages have been implicated as the cellular source of IL-10 in measles patients (37), and recent studies have shown that CD4 ϩ CD25 ϩ Treg secrete IL-10 and can be a major mediator of immune suppression in infection (38,39). To determine whether CD14 ϩ monocyte/macrophages and/or CD4 ϩ CD25 ϩ T cells could be responsible for the elevated plasma IL-10, and whether MV treatment results in an increase in their cell number, we treated PBMC from healthy donors with MV (MOI ϭ 1) or Vero-SLAM cell lysate (mock) followed 3 days later by PMA, ionomycin, and brefeldin A stimulation for 3 h before FACS analysis (Fig.…”
Section: Up-regulates Il-10-producing Cd14mentioning
confidence: 99%
“…In addition to a3, the Tcirg1 gene mutated in oc/oc mice encodes another protein called TIRC7 and representing, in mouse, a marker of regulatory T-cell subsets. 49 However, because expression of TIRC7 and distribution of TIRC7 ϩ regulatory T cells are not altered in oc/oc mice (A.W., unpublished data, 2006), it is doubtful that the Tcirg1 mutation directly affects T-cell phenotype. More probably, this Th17 phenotype could result from the modifications of the bone microenvironment and cellular interactions resulting from osteopetrosis.…”
mentioning
confidence: 99%